Del sonido del Pueblo a los ecos del pasado: Las versiones de La pasión según Trelew, de Tomás Eloy Martínez (1973-2009) - García, Victoria Gisele (2020)
La pasión según Trelew occupies a paradoxical place in the work of Tomás Eloy Martínez. On the one hand, it is the book that changed the author's life, as he himself has described it, and the only one whose writing process went through practically all the stages of his literary work: it originally appeared in 1973 and was re-edited in 1997 and 2009, each time with textual variations introduced by the author. On the other hand, the book seems to constitute the crystallization of a concept of writing, based on trust in absolutes and on the militant confrontation between the true and the false, from which the writer sought to distance himself in later on his career. In this article, we propose to analyze the way in which this displacement is reflected in the different versions of the book. We will see that the versions of 1997 and 2009 tend to dilute the confrontation between truth and falsehood that initially shaped the account of the events that took place in Trelew in 1972. Likewise, the rewritings detract from the People's role as a collective subject that provided the basis for the confrontation between truth and lie that organized the text.